Does bleeding affect patient‐reported outcome measures in patients with myelodysplasia or hematologic malignancies: a systematic review. Issue 4 (10th October 2013) - Estcourt, Lise J.; Pinchon, Deborah; Symington, Emily; Kelly, Anne M.; Doree, Carolyn; Brunskill, Susan; Glidewell, Liz; Stanworth, Simon
<x xml:space="preserve">Abstract</x> Background Relatively minor bleeding (e.g., bruising and/or petechiae) may cause patient distress. This systematic review's objective was to assess whether bleeding affects health‐related quality of life (HRQoL) or illness perceptions or representations (IPs) in patients with hematologic malignancies or myelodysplasia (MDS). Study Design and Methods We searched, in full, 12 electronic databases (including CENTRAL, MEDLINE, and EMBASE) up to January 7, 2013, for eligible randomized controlled trials (RCTs), prospective cohort studies, and cross‐sectional studies. Results A total of 6247 studies were initially identified; 5945 studies were excluded on the basis of the abstract. A total of 302 full‐text articles were evaluated independently by two reviewers; of these, six studies within seven citations were eligible for inclusion. Two studies are still in progress, four studies within five citations were included in this review (one RCT, one prospective observational study, one interview study, and one Web‐based survey). None of the included studies were designed to assess the impact bleeding had on HRQoL or IPs. The Web‐based survey and observational study used two new patient‐reported outcome scales which specifically assessed patient distress or concern due to bleeding. The majority of patients within these two studies either did not experience bleeding or did not have severe thrombocytopenia. Conclusion There is insufficient evidence to demonstrate whether bleeding is a significant clinical problem that affects patients' HRQoL or IPs in either patients with MDS or patients with hematologic malignancies. Rigorously designed studies to assess the scale of this problem in both of these groups of patients are required.